2022
DOI: 10.3389/fvets.2022.961583
|View full text |Cite
|
Sign up to set email alerts
|

Hematological and biochemical indices, growth performance, and puberty of goats fed with Mombasa and blue panic as salt-tolerant alternatives to alfalfa under arid conditions

Abstract: The objective of this study was to evaluate the impact of Mombasa or blue panic as a salt-tolerant alternative to alfalfa on growth performance, puberty, blood hematology, serum metabolites, and serum mineral profile in growing goats. Twenty-four growing goats of 4 months old age with 14.45 ± 0.6 kg average body weight were assigned to three treatment diets with 8 animals per treatment. Weights of each animal were measured at the onset of the trial and subsequently on a weekly basis until the end of the trial … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
1
1

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 34 publications
0
1
1
Order By: Relevance
“…However, Malecky et al (2016) revealed a wider reference range for the glucose levels in the blood of Mehraba sheep (66.9–116.5 mg/dl). Whereas [ 22 ] obtained lower blood glucose levels in goats (33.15–47.26 mg/dl), nevertheless [ 23 ] reported greater blood glucose concentrations in wild goats (126.1 mg/dl) than the findings obtained in this study. Meanwhile, glucose levels are lower than the typical range; this threshold implies hypoglycemia, though elevated levels signal hyperglycemia [ 24 ].…”
Section: Discussioncontrasting
confidence: 87%
“…However, Malecky et al (2016) revealed a wider reference range for the glucose levels in the blood of Mehraba sheep (66.9–116.5 mg/dl). Whereas [ 22 ] obtained lower blood glucose levels in goats (33.15–47.26 mg/dl), nevertheless [ 23 ] reported greater blood glucose concentrations in wild goats (126.1 mg/dl) than the findings obtained in this study. Meanwhile, glucose levels are lower than the typical range; this threshold implies hypoglycemia, though elevated levels signal hyperglycemia [ 24 ].…”
Section: Discussioncontrasting
confidence: 87%
“…Moreover, WBC, RBC, MCH, MCHC, Hb, and PCV ( 58 ) values were not influenced by goats supplemented with Lablab purpureus and Vigna unguiculata . Furthermore, PCV, Hb, RBC, MCH, MCHC, and WBC ( 59 ) values were not affected by goat fed Mombasa or blue panic as a salt-tolerant alternative to replacing Alfalfa. PCV, Hb, RBC, MCV, MCH, and MCHC ( 60 ) values were not affected by West African Dwarf goats fed varying levels of treated sweet orange peels.…”
Section: Discussionmentioning
confidence: 92%